2018
DOI: 10.1007/s12602-017-9382-7
|View full text |Cite
|
Sign up to set email alerts
|

Strain Screening from Traditional Fermented Soybean Foods and Induction of Nattokinase Production in Bacillus subtilis MX-6

Abstract: The plasminogen-free fibrin plate assay method was used to isolate Bacillus subtilis MX-6, a strain with high production of nattokinase from Chinese douchi. The presence of aprN, a gene-encoding nattokinase, was verified with PCR method. The predicted amino acid sequence was aligned with homologous sequences, and a phylogenetic tree was constructed. Nattokinase was sublimated with ammonium sulfate, using a DEAE-Sepharose Fast Flow column, a CM-Sepharose Fast Flow column and a Sephadex G-75 gel filtration colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
2
16
1
Order By: Relevance
“…Due to the high amino acid concentrations in TPW, the role of amino acid-induced enzyme production in TPW can be excluded. This standpoint is consistent with other researchers, such as Li-Li Man, who suggested that the peptide component in the soybean peptone was a critical factor in facilitating the synthesis of nattokinase rather than amino acids [17].…”
Section: Discussionsupporting
confidence: 92%
“…Due to the high amino acid concentrations in TPW, the role of amino acid-induced enzyme production in TPW can be excluded. This standpoint is consistent with other researchers, such as Li-Li Man, who suggested that the peptide component in the soybean peptone was a critical factor in facilitating the synthesis of nattokinase rather than amino acids [17].…”
Section: Discussionsupporting
confidence: 92%
“…NK was extracted from traditional fermented food using B. subtilis natto (Sumi et al 1987) [17]. The effects of NK on thrombosis have been confirmed in previous studies.…”
Section: Discussionmentioning
confidence: 90%
“…A single dose of nattokinase administration showed the enhanced fibrinolysis and anticoagulation profiles (Kurosawa et al., 2015). Nattokinase is mainly produced by the Bacillus subtilin (natto) during the fermentation of soybeans or soybeans‐based ingredients to produce Natto‐containing foods (Cai et al., 2017; Man et al., 2019). Now, Nattokinase is typically used as a functional factor in health functional food to prevent cardiovascular diseases and thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Natto-containing foods (Cai et al, 2017;Man et al, 2019). Now, Nattokinase is typically used as a functional factor in health functional food to prevent cardiovascular diseases and thrombosis.…”
mentioning
confidence: 99%